2011
DOI: 10.1111/j.1365-2427.2010.02568.x
|View full text |Cite
|
Sign up to set email alerts
|

Planktivory in the changing Lake Huron zooplankton community: Bythotrephes consumption exceeds that of Mysis and fish

Abstract: 1. Oligotrophic lakes are generally dominated by calanoid copepods because of their competitive advantage over cladocerans at low prey densities. Planktivory also can alter zooplankton community structure. We sought to understand the role of planktivory in driving recent changes to the zooplankton community of Lake Huron, a large oligotrophic lake on the border of Canada and the United States. We tested the hypothesis that excessive predation by fish (rainbow smelt Osmerus mordax, bloater Coregonus hoyi) and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
73
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(77 citation statements)
references
References 66 publications
(110 reference statements)
1
73
3
Order By: Relevance
“…These findings show a cascading impact of Bythotrephes that has not been previously documented in other lakes (21) and that is unusually large for an invertebrate predator (28). Possibly, this effect is related to the feeding mode of Bythotrephes vs. other invertebrate predators (18,29,30), and this topic could be addressed by additional research.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings show a cascading impact of Bythotrephes that has not been previously documented in other lakes (21) and that is unusually large for an invertebrate predator (28). Possibly, this effect is related to the feeding mode of Bythotrephes vs. other invertebrate predators (18,29,30), and this topic could be addressed by additional research.…”
Section: Resultsmentioning
confidence: 99%
“…The spiny water flea, Bythotrephes longimanus (hereafter Bythotrephes), which is nonnative in North America, is a voracious zooplanktivore that has the capacity to consume more zooplankton than fish and other invertebrate planktivores combined (18). Despite this planktivory and large documented ecological impacts on zooplankton communities (19,20), Bythotrephes has not been found to have cascading effects on lake primary production and water clarity (21).…”
mentioning
confidence: 99%
“…These filter feeders contributed to dramatic reductions in water column light attenuation, phosphorous levels, and chlorophyll concentrations in Saginaw Bay . Further, heightened planktivory by the invasive invertebrate Bythotrephes longimanus may exert a structuring influence on zooplankton communities in Lake Huron (Bunnell et al 2011).…”
Section: Introductionmentioning
confidence: 98%
“…Recent studies have suggested that Bythotrephes can consume large portions of zooplankton productivity (Strecker & Arnott, 2008;Bunnell et al, 2011), yet a number of planktivorous fish may avoid consuming Bythotrephes (Barnhisel & Kerfoot, 2004) or experience lower net growth because Bythotrephes spines occupy gut space but have no nutritional value (Parker Stetter et al, 2005), resulting in an overall loss of food available to planktivores. This reduced availability of energy may drive planktivores to forage on other resources, such as large-bodied Leptodora.…”
Section: Discussionmentioning
confidence: 98%